REKONSTRUKSI PENDIDIKAN ISLAM BERBASIS INKLUSIVITAS DAN MULTIKULTURALISME: PENDEKATAN BARU UNTUK MEMBANGUN TOLERANSI DI INDONESIA - Ghazza Jaudat Fastmadhi; Nazwa Svenska Aulia Fastmadhi; Deddi Fasmadhy (Jurnal Cakrawala Ilmiah, 2024)
Islamic Education in Indonesia is often perceived as exclusive and less capable of instilling values of inclusivity and multiculturalism. The current education system tends to emphasize the singular truth of one religious group while marginalizing others, leading to the growth of intolerance and radicalism among students. This research aims to address this gap by proposing a reconstruction of Islamic education based on inclusivity and more effective multiculturalism. Using a library research method, this study explores curriculum design, the role of educators, and teaching strategies that can be implemented in Islamic education to promote tolerance and openness towards cultural and religious diversity. The findings suggest that Islamic education should adopt a dialogical-persuasive approach and contextual interpretation of religious texts to encourage critical thinking and tolerant attitudes. Additionally, innovative teaching strategies, such as group discussions and interfaith collaboration, need to be implemented to create an inclusive educational environment. The conclusion of this research highlights the importance of overhauling key components of Islamic education, including the curriculum, educators, and teaching methods, to foster a more harmonious and multicultural society. This reconstructive effort is expected to serve as a foundation for transforming the national education paradigm into one that is more inclusive and relevant to contemporary challenges.